The relationship between cardio‐ankle vascular index and subclinical atherosclerosis evaluated by cardiac computed tomographic angiography. Issue 8 (8th March 2017) - Matsumoto, Suguru; Nakanishi, Rine; Luo, Yanting; Kim, Michael; Alani, Anas; Nezarat, Negin; Dailing, Christopher; Budoff, Matthew J.
Abstract : Background: The cardio‐ankle vascular index (CAVI) is a new noninvasive index to evaluate arterial stiffness. We investigated whether CAVI can predict severity, extent, and burden of coronary artery disease by comparing results with cardiac computed tomographic angiography (CCTA). Hypothesis: CAVI may predict the presence of subclinical atherosclerosis. Methods: We prospectively enrolled 95 patients (66% male; mean age, 50 ± 16 years) who underwent both CCTA and CAVI consecutively. We evaluated if CAVI correlated with (1) severe stenosis (≥50%); (2) plaque extent, determined by a segment‐involvement score (SIS), defined by the total number of coronary artery segments containing any plaque; and (3) plaque burden, determined by a segment‐stenosis score (SSS), defined by the extent of obstruction of coronary luminal diameter in individual coronary artery segments. Results: Bivariate analysis showed a statistically significant relationship not only between CAVI and SIS, but also between CAVI and SSS ( r 2 = 0.4, P < 0.0001 for SIS; r 2 = 0.36, P < 0.0001 for SSS). Multivariable logistic analysis demonstrated that CAVI is significantly associated with SSS >5 (odds ratio [OR]: 2.3, 95% confidence interval [CI]: 1.1‐7.8, P = 0.03) and SIS >5 (OR: 2.3, 95% CI: 1.1‐5.8, P = 0.02), but not severe stenosis (OR: 1.7, 95% CI: 0.9‐4.3, P = 0.13), after adjusting for age, sex, chest pain, hypertension, dyslipidemia, family history, diabetes, and current smoking. Conclusions: We demonstrated that CAVI had a significant relationship with subclinical coronary atherosclerosis evaluated by CCTA, especially in relation to plaque burden and plaque extent, but not severe stenosis. Thus, CAVI may reflect coronary atherosclerosis burden more than severity.